Stalin's outcasts : aliens, citizens, and the Soviet state, 1926 - 1936 - Alexopoulos, Golfo (Cornell University Press, 2003)
Marking outcasts and making citizens -- Faces of the disenfranchised -- Dangers, disappearances, and false appearances -- Hardship and citizenship -- The talents and traits of Soviet citizens -- Endings and enduring legacies